(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
By virtue of the KP hierarchy reduction method, the N-dark soliton solutions of the multi-component Maccari system are constructed. Taking the coupled Maccari system for instance, the N-dark soliton solutions are further obtained in terms of determinants. In addition, in contrast with bright-bright soliton collisions, the dynamical analysis shows that the collisions of dark-dark solitons are elastic and there is no energy exchange among solitons in different components. What's more, we also investigate the dark-dark soliton bound states including stationary and moving ones.